RETRACTED: Protein kinase C is a calcium sensor for presynaptic short-term plasticity - Fioravante, Diasynou; Chu, YunXiang; de Jong, Arthur PH; Leitges, Michael; Kaeser, Pascal S; Regehr, Wade G (eLife, 2014)
In presynaptic boutons, calcium (Ca2+) triggers both neurotransmitter release and short-term synaptic plasticity. Whereas synaptotagmins are known to mediate vesicle fusion through binding of high local Ca2+ to their C2 domains, the proteins that sense smaller global Ca2+ increases to produce short-term plasticity have remained elusive. Here, we identify a Ca2+ sensor for post-tetanic potentiation (PTP), a form of plasticity thought to underlie short-term memory. We find that at the functionally mature calyx of Held synapse the Ca2+-dependent protein kinase C isoforms α and β are necessary for PTP, and the expression of PKCβ in PKCαβ double knockout mice rescues PTP. Disruption of Ca2+ binding to the PKCβ C2 domain specifically prevents PTP without impairing other PKCβ-dependent forms of synaptic enhancement. We conclude that different C2-domain-containing presynaptic proteins are engaged by different Ca2+ signals, and that Ca2+ increases evoked by tetanic stimulation are sensed by PKCβ to produce PTP.
Keywords: post-tetanic potentiation; short-term plasticity; protein kinase C; synaptotagmin; phorbol ester; calcium